From Health to Financial Problems: Multiproblems Among Victims of Partner and Non-Partner Physical Violence, and Matched Nonvictims - van der Velden, Peter G. (Journal of interpersonal violence, 2021)
Previous research suggests that victims of partner physical violence (PPV) often face multiple distinct problems, but comparative population-based studies focusing on the prevalence of multiple problems are lacking. Aim of the present study is to gain insight in the prevalence of multiple problems among individuals victimized by PPV in the past 12 months, compared with matched nonvictims and victims of non-partner physical violence (non-PPV). For this purpose, data were extracted from two population-based surveys conducted in 2018 and 2019 on potentially traumatic events in the Netherlands. We focused on problems identified in previous studies on PPV and non-PPV and related problems, varying from physical health, mental health, financial and legal problems, to lack of social support and being exposed to other potentially traumatic and stressful life events (LFEs). In total, 49 respondents were victimized by PPV and 89 by non-PPV in the past 12 months. They were compared with pairwise matched groups not affected by any traumatic or stressful LFEs in this period (nPPV victims comparison group = 245, nnon-PPV comparison group = 445). Results showed that PPV victims significantly more often faced all 12 distinct problems than matched nonvictims (2.31 ≤ odds ratio [OR] ≤ 15.48) and non-PPV victims (2.12 ≤ OR ≤ 4.52). PPV victims more often had any problem than non-PPV victims (OR = 8.19), but no significant differences were found between PPV and non-PPV victims with regard to mental health problems. Findings stress the necessity of a multidisciplinary coordinated community response to help PPV victims.